THE INFLUENCE OF LOCUS OF CONTROL AND INDUSTRY WORK PRACTICE TO WORK READINESS - Andini Kusumaningsih; Dedi Purwana; Suherdi (Transpublika Publisher, 2023)
Locus of control refers to an individual's belief in their ability to control and influence outcomes in their lives. It can be categorized as internal (personal control) or external (attributing outcomes to external factors). This study aims to investigate the impact of locus of control and industrial work practices on work readiness among twelfth-grade students at SMKN 50 Jakarta. The study uses a quantitative approach with multiple linear regression analysis using IBM SPSS 24.0 software. A Likert scale questionnaire is used for the survey method. The accessible population for the study is 211 students, with a sample size of 138 students determined using the Slovin formula and a 5% margin of error. Proportionate stratified random sampling is used as the sampling technique. The data analysis procedure includes: 1.) Analysis of test requirements through normality and reliability tests; 2.) Examination of classical assumptions involving tests for multicollinearity and heteroscedasticity; 3.) Multiple regression analysis; 4.) Hypothesis testing using the F-test and T-test; and 5.) Evaluation of the coefficient of determination. The findings show a positive and significant influence between locus of control, industrial work practices, and job readiness. The coefficient of determination indicates that 41.0% of the variability is explained by the variables studied, while the remaining 59% is influenced by external factors beyond the scope of this study.